Effect of tirasemtiv, a selective activator of the fast skeletal muscle troponin complex, in patients with peripheral artery disease. (August 2014) - Bauer, Timothy A; Wolff, Andrew A; Hirsch, Alan T; Meng, Lisa L; Rogers, Kevin; Malik, Fady I; Hiatt, William R
Tirasemtiv (CK-2017357), a novel small-molecule activator of the fast skeletal muscle troponin complex, slows the rate of calcium release from troponin, thus sensitizing fast skeletal muscle fibers to calcium. In preclinical studies, tirasemtiv increased muscle force and delayed the onset and reduced the extent of muscle fatigue during hypoxia in vitro and muscle ischemia in situ. This study evaluated the effect of single doses of tirasemtiv on measures of skeletal muscle function and fatigability in patients with stable calf claudication due to peripheral artery disease (PAD). Sixty-one patients with an ankle–brachial index ≤0.90 in the leg with claudication received single double-blind doses of tirasemtiv 375 mg and 750 mg and matching placebo in random order about 1 week apart. After 33 patients were treated, the 750 mg dose was decreased to 500 mg due to adverse events and these dose groups were combined for analysis. On each study day, bilateral heel-raise testing was performed before and at 3 and 6 hours after dosing; a 6-minute walk test was performed at 4 hours after dosing. Claudicating calf muscle performance was increased at the highest dose and plasma concentration of tirasemtiv; however, the 6-minute walk distance decreased with both the dose and plasma concentration of tirasemtiv, possibly due to dose-related adverse events, particularly dizziness, that could impede walking ability. In conclusion, the mechanism of fast skeletal muscle troponin activation improved muscle function but not 6-minute walking distance in patients with claudication due to PAD.ClinicalTrials.gov Identifier: NCT01131013